(untitled) (Baghdad Science Journal, 2020)
Ruthenium-Ruthenium and Ruthenium–ligand interactions in the triruthenium "[Ru3(μ-H)(μ3-κ2-Hamphox-N,N)(CO)9]" cluster are studied at DFT level of theory. The topological indices are evaluated in term of QTAIM (quantum theory of atoms in molecule). The computed topological parameters are in agreement with related transition metal complexes documented in the research papers. The QTAIM analysis of the bridged core part, i.e., Ru3H, analysis shows that there is no bond path and bond critical point (chemical bonding) between Ru(2) and Ru(3). Nevertheless, a non-negligible delocalization index for this non-bonding interaction is calculated. The interaction in the core Ru3H can be described as a (4centre–4electron) type. For Ru-N (oxazoline ring) bond, the calculated topological data propose a pure σ-bond. The computed topological parameters of oxazoline ligand reveal the presence of slightly some double bond characters within ligand ring.